Perancangan Sistem Informasi Monitoring Dan Pengelolaan Inventaris Sarana Prasarana Sekolah SMK N 1 Gadingrejo - Feriyanto, Deny; Puspitasari, Tuti (YHMM PUBLISHING, 2024)
The management of infrastructure and facility inventories is a crucial aspect in supporting the educational process in schools. At SMK N 1 Gadingrejo, inventory data collection and asset monitoring are still conducted manually, which poses risks such as data loss, inefficient management, and difficulties in tracking asset conditions and usage. To address these issues, this study aims to design a technology-based information system that facilitates integrated inventory monitoring and management. A structured modeling approach is applied in the system design, including Context Diagrams, DFD Level 0 and Level 1, and ER-Diagrams to represent data flow and relationships between entities. The result of this research is a web-based system that enables school staff, such as administrators and administrative personnel, to record inventory items, monitor asset conditions, and generate reports automatically. The implementation of this system is expected to improve efficiency, reduce manual errors, and streamline asset management processes. Furthermore, the system can be developed with additional features such as RFID or QR code-based asset tracking, mobile application integration, and automatic maintenance notifications. With further development, this system has the potential to provide a more comprehensive solution and support real-time facility and infrastructure management.